Evaluation of leptin levels in serum as a biomarker for suicide behavior: systematic review and meta-analysis. (2nd January 2021) - González-Castro, Thelma Beatriz; Almeida de la O, Perla de los Angeles; Tovilla-Zárate, Carlos Alfonso; López-Narváez, María Lilia; Genis Mendoza, Alma Delia; Juárez-Rojop, Isela Esther; Pérez-Hernández, Nonanzit; Rodriguez-Perez, José Manuel
Abstract: Objective: We conducted a meta-analysis of case-control studies to determine whether leptin levels in serum contribute to the pathogenesis of suicide behavior. Methods: PubMed, EBSCO and Science Direct databases were used to search for relevant articles published before January 2020. The systematic review included nine case-control studies that measured leptin levels. The standardized mean difference ( d ) and 95% confidence intervals were calculated in a fixed-effects model and a random-effects model when appropriate. Results: The results of our meta-analysis indicated that individuals with suicide behavior presented reduced levels of leptin ( d : −1.80, 95% CI: −2.21 to −01.38 n g/ml, I 2 = 0, p(Q) = 0.59). Sensitivity and publication bias analyses confirmed these results. Conclusions: The current meta-analysis suggests that leptin levels might be associated with an increased risk of suicide behavior. However, more studies including larger sample sizes are needed to reach conclusive result.